Children’s preferences for features and designs of KN95-style respirators: A comparative study between Indonesia and Nepal - Sarah Nila; Chandika Shrestha; Hastin M. Maharti; Claire J. Horwell; Dicky C. Pelupessy; Rachel L. Kendal; Meghnath Dhimal; Judith Covey (PLoS ONE, 2025)
Air pollution is a global crisis, posing significant health risks to humans. Children are particularly vulnerable to the effects of particulate air pollution, and the use of respiratory protection could reduce their exposure. Certified, well-fitting respirators have been shown to effectively filter airborne particles and are increasingly available for children in non-occupational settings. However, their effectiveness relies on proper fit and consistent use. Understanding children’s perspectives on wearing respiratory protection, specifically their preferences for different types and styles of respirators, is crucial. To explore these issues, 12 focus group discussions were conducted in January 2023 with 116 children aged 6–12 years living in Kathmandu, Nepal (N = 67) and Bandung, Indonesia (N = 49). Participants were recruited from public and private schools in each city using purposive sampling to ensure diversity in age, gender and socio-economic background. Focus groups were held in school settings and facilitated by local researchers in the children’s native languages. Children were shown seven different respirators and asked questions about their preferred styles and features. Statistical analyses using Wilcoxon one-sample tests and ordinal regression showed the most popular types of respirators had ear-loops rather than head-straps and some features (e.g., patterned rather than plain masks) were more popular with certain groups (e.g., younger children). These results suggest that respirator manufacturers should ideally offer a variety of styles or designs.